Hydrothermal synthesis of rGO and MnCoS composite for enhanced supercapacitor application - Manikandan M.; Prasankumar T.; Manikandan E.; Papanasam E.; Ramesh K.; Ramesh S. (Nature Research, 2025)
Nanostructured materials incorporating transition metal sulfides have demonstrated considerable potential across various applications, particularly in the realms of energy production and storage. Sulfide-based material preparation is a challenging and costly procedure that requires a high temperature and reducing atmosphere. This work reports that manganese cobalt sulfide (MCS) and reduced graphene oxide composite manganese cobalt sulfide (rMCS) were successfully prepared through a hydrothermal method. Various characterization techniques were employed to analyze the prepared materials, including X-ray diffraction, field emission scanning electron microscopy, transmission electron microscopy, Brunauer-Emmett-Teller analysis, and X-ray photoelectron spectroscopy. In a three-electrode system, MCS and rMCS electrodes exhibit an excellent specific capacitance of 1695 and 1925F g?1 at 1A g?1 current density respectively. MCS delivers the capacitance retention of 99% and rMCS exhibits the capacitance retention of 100% capacitance retention over 5000 consecutive cycles. The constructed asymmetric supercapacitor electrode (rMCS//rGO) exhibits the energy and power density of 64 Wh kg?1 at 799W kg?1, respectively with outstanding cyclic stability of 97.4% even after 10,000 cycles. The exceptional electrochemical properties of MCS with rGO composite electrode indicate that they would make an outstanding electrode material for cutting-edge energy storage devices. ? The Author(s) 2024.